African Activism Through Pugwash - Nola Dippenaar; Joelien Pretorius (The Thinker, 2024)
The Pugwash Conferences on Science and World Affairs grew from the Russell-Einstein Manifesto initiative in 1955 to become an amorphously structured transnational movement of natural and social scientists with a primary focus on the dangers of nuclear weapons. Pugwash, together with Sir Joseph Rotblat, a founding member and long-serving secretary-general and later president, won the Nobel Peace Prize in 1995 for its role in highlighting these dangers. It did so through its annual conferences that brought together scientists, government officials and observers from across the world, as well as its workshops and publications, and behind-the scenes interventions towards conflict resolution. The history and role of Pugwash has been the subject of many publications, but none of them pay adequate attention to Africans’ participation in Pugwash, if at all. And yet, a preliminary review of the quinquennial annals and newsletters that Ezume summarise the activities of Pugwash suggests that African scientists’ involvement in the annual conferences was significant. Africans also organised regional workshops on issues of special interest to the continent and jointly published with other Pugwash members. National chapters were established in several African countries and over the course of two decades, a Pan-African Pugwash group held at least six meetings and published some of these meetings’ proceedings. This opinion piece is based on a preliminary exploratory effort to highlight how Africans engaged the Pugwash movement, to know more about the impact that Africans had in Pugwash and Pugwash had in Africa, and to look to the future—to encourage science activism and youth participation in peace and anti-nuclearism on the continent. We start off with a short introduction of Pugwash, telling its origin story and then proceed to Africans’ participation in and adoption of Pugwash to exercise peace activism.